2003
DOI: 10.1007/bf02931512
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of sulfonphthalein dyes by manganese peroxidase activity of the white-rot fungusPhanerochaete chrysosporium

Abstract: Manganese peroxidase (MnP) was produced by shallow stationary cultures of Phanerochaete chrysosporium growing on N-limited medium. Decolorization of sulfonphthalein (SP) dyes by MnP was investigated. The MnP activity profile and decolorization of SP dyes was correlated and almost all dyes were decolorized at pH 4.0. The influence of various inhibitors on Bromocresol Purple decolorization suggested an oxidative nature of the MnP-catalyzed decolorization of SP dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…The order of preference for SP dyes as substrate for MnP was Phenol Red (Christian et al 2003;Shrivastava et al 2005). Harazono and Nakamura (2005) investigated the decolorization of mixtures of four reactive textile dyes, including azo and anthraquinone dyes, by a white-rot basidiomycete Phanerochaete sordida.…”
Section: Peroxidasesmentioning
confidence: 99%
“…The order of preference for SP dyes as substrate for MnP was Phenol Red (Christian et al 2003;Shrivastava et al 2005). Harazono and Nakamura (2005) investigated the decolorization of mixtures of four reactive textile dyes, including azo and anthraquinone dyes, by a white-rot basidiomycete Phanerochaete sordida.…”
Section: Peroxidasesmentioning
confidence: 99%
“…There are several reports of microorganisms capable of decolorizing synthetic dyes. This has been attributed to their growth and production of enzymes such as laccase (1,9,40), azoreductases (3), and peroxidases, for example, lignin peroxidase (12,25,36), manganese peroxidase (10,38), and versatile peroxidase (16). However, most of the synthetic dyes are xenobiotic compounds that are poorly degraded using the typical biological aerobic treatments.…”
mentioning
confidence: 99%
“…They are one of the most studied enzymes because of their inherent spectroscopic properties and potential use in both diagnostic and bioindustrial applications. In particular, their ability to degrade a wide range of substrates has recently stimulated interest in their potential application in environmental bioremediation of recalcitrant and xenobiotic wastes (10,25,26).…”
mentioning
confidence: 99%
“…However, the decolorization of textile and other dyes by BGP in presence of 1.0 mM HOBT appeared without the formation of any precipitate. It suggested that the decolorization of dyes took place via degradation of aromatic ring of the compounds or by cleaving certain functional groups as reported elsewhere (Christian et al, 2003;Husain et al, 2009). HOBT could have a dual role, first as a mediator by increasing the substrate range of dyes for BGP and second enhancing the rate of oxidation.…”
Section: Dye Color Removal With Bitter Gourd (Momordica Charantia) Pementioning
confidence: 98%